(untitled) (Bangladesh Journal of Anatomy, 2020)
Context: Age has to be determined not only for identification purpose but also for various civil and criminal purposes. Timing of epiphyseal fusion is an important means to estimate the age of adolescents and young adults. The present study was conducted to determine age of fusion of lower end of radius. Materials and Methods: This cross sectional descriptive type of study was carried out in the Department of Anatomy, Rajshahi Medical College from July 2018 to June 2019. Total number of subjects was 88 age ranging from less than one year to twenty one years. Radiographs (A-P view) of both hands including wrist joint were studied. Result: In this study complete fusion of lower end of radius was found to occur at 17-18 years. There was no appreciable difference in the age of fusion between right and left side. Bangladesh Journal of Anatomy January 2020, Vol. 18, No. 1, pp. 12-16